2010
DOI: 10.1159/000319580
|View full text |Cite
|
Sign up to set email alerts
|

Multidetector Row Computed Tomography to Assess Changes in Airways Linked to Asthma Control

Abstract: Background: In asthma, multidetector row computed tomography (MDCT) detects abnormalities that are related to disease severity, including increased bronchial wall thickness. However, whether these abnormalities could be related to asthma control has not been investigated yet. Objective: Our goal was to determine which changes in airways could be linked to disease control. Methods: Twelve patients with poor asthma control were included and received a salmeterol/fluticasone propionate combination daily for 12 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Multidetector row CT demonstrated that a salmeterol/fluticasone combination did not significantly change either WA or Ai in patients with poor asthma control [37]. We may find that omalizumab, as an add-on to current asthma therapy, offers a potential explanation for decreasing airway wall thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Multidetector row CT demonstrated that a salmeterol/fluticasone combination did not significantly change either WA or Ai in patients with poor asthma control [37]. We may find that omalizumab, as an add-on to current asthma therapy, offers a potential explanation for decreasing airway wall thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Kurashima et al used CT to evaluate the efficacy of inhaled corticosteroid and found a decrease in airway wall thickness among asthmatic patients with duration of symptoms less than 3 years, a minor response among 3 to 5 years and no change in wall thickness in patients with more than 5 years duration of disease [ 41 ]. However, Brillet et al did not found any change of both WA and LA after a combination of salmeterol/flucitasone daily for 12 weeks, though patients displayed clinical and functional improvement, assessed by a decrease in FEV1 and expiratory reserve volume (ERV) [ 42 ].…”
Section: Quantitative Ct In Asthmamentioning
confidence: 99%
“…forced expiratory volume in 1 s (FEV 1 ) and peak expiratory flow (PEF)] performed in these studies did not provide a comprehensive evaluation of the entire bronchial tree as they lack sufficient resolution to describe subtle changes in the small airways [5,6]. This has prompted the need for developing new image-based [7,8] techniques capable of detecting functional changes occurring in the more distal part of the lung following the administration of drugs able to reach and treat small airways [9,10,11]. …”
Section: Introductionmentioning
confidence: 99%